MODEL LAYANAN TRANSPORTASI UNTUK MENARIK MINAT WISATAWAN BERKUNJUNG KE OBYEK WISATA DI JAWA TIMUR - Herman Moeis; Ali Fahmi (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
The number of foreign tourists traveling in Indonesia in 2004 grew by 19.1% compared to 2003. While foreign exchange earnings reached U.S. $ 4.798 billion, up 18.8% of revenue in 2003 was 4.037 billion. Based on the record while the center of Statistic Bureau, the number of foreign tourists to Indonesia in 2005 totaled 5.007 million or a decline of 5.90%. Talking about tourism one should also discuss the transportation or transportation. Is something that is not possible if the age of the ultra modern, there are people do not get a tour of adequate transport facilities. Can be said that the tourists that travel is already a manifestation of the interaction, as a result of displacement of people from the place where he usually lived. Transportasilah that can move a lot of people, from one State to another State, from one region to another and from one city to another and from cities to the countryside and vice versa. (http://www.kabarindonesia.com?berita.php?pil) In the descriptive qualitative research, process analysis and interpretation of data not only at the end of data collection or stand alone, but also simultaneously carried out during field data collection takes place, resulting in qualitative research is often known as a cyclic process. The results obtained are: Accessibility merupkaan important factor in supporting tourism activities, due to the ease of accessibility to the shorter distance and travel time more efficiently. Ease of access mimur either through air, sea and land to the development of tourism opportunities member. Land transport network in East Java have been integrated, biik connecting cities in the province as well as with other provinces. For sea transportation between islands connecting the port of Tanjung Perak is available and Tanjung Wangi. While air transportation is available Juanda International Airport connecting major cities in the country and abroad.